Decentralized Control for the Interconnected Time-Delay Singular/Nonlinear Subsystems with Closed-Loop Decoupling Property. (1st April 2015) - Hu, Nien-Tsu; Wu, Ter-Feng; Xu, Sendren Sheng-Dong; Tsai, Pu-Sheng
Abstract : This paper presents the decentralized trackers using the observer-based suboptimal method for the interconnected time-delay singular/nonlinear subsystems with closed-loop decoupling property. The observer-based suboptimal method is used to guarantee the high-performance trajectory tracker for two different subsystems. Then, due to the high gain that resulted from the decentralized tracker, the closed-loop system will have the decoupling property. An illustrative example is given to demonstrate the effectiveness of the proposed control structure.